STATISTICAL INFORMATION ON THE INCIDENCE OF KIDNEY INJURY IN PATIENTS WITH COVID-19 - Khamdamov, B.Z.; Khursandov, I.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
The SARS-CoV-2 coronavirus has turned into a life-threatening pandemic disease - COVID-19. It is known that the main manifestations of this disease are acute respiratory distress syndrome and diffuse alveolar damage. Although the respiratory system is the primary target of SARS-CoV-2, other organs in the body can be affected by the virus through the circulatory system. Initially, information about kidney damage was very scarce. Publications regarding kidney damage in SARS-CoV-2 at the early stage of the pandemic were not systemic and were characterized by scattered clinical cases ranging from mild proteinuria to progressive acute renal failure. The first statistics on the incidence of kidney damage in patients who have had SARS-CoV-2 were presented by scientists at the Yale University School of Medicine based on a study of 1.6 clinical cases. According to their data, 24-57% of hospitalised patients have kidney complications after coronavirus and during the disease.